2002
DOI: 10.1038/sj.sc.3101249
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation ileocystoplasty in patients with neurogenic bladder due to spinal cord injury or spina bifida

Abstract: Study design: Retrospective analysis of augmentation ileocystoplasty for neurogenic bladder. Objectives: To analyze the eects and complications of augmentation ileocystoplasty in patients with neurogenic bladder due to spinal cord injury (SCI) or spina bi®da retrospectively. Setting: Department of Urology, Kanagawa Rehabilitation Hospital, Japan. Methods: We have treated 11 patients with neurogenic bladder due to SCI and 10 patients with spinal bi®da with augmentation ileocystoplasty since 1989. The purpose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 12 publications
1
36
0
1
Order By: Relevance
“…The results of each paper included in this review will be summarised and critically analysed. Of the 14 articles reviewed, two (Nomura et al, 2002;Mitsui et al, 2008) discussed the surgical technique used. Mitsui et al (2008) used more than one technique (Hautmann, Goodwin and hemi-Kock) but made no reference of any difference to outcome.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of each paper included in this review will be summarised and critically analysed. Of the 14 articles reviewed, two (Nomura et al, 2002;Mitsui et al, 2008) discussed the surgical technique used. Mitsui et al (2008) used more than one technique (Hautmann, Goodwin and hemi-Kock) but made no reference of any difference to outcome.…”
Section: Resultsmentioning
confidence: 99%
“…The age range of children and young adults in the included studies was 0·25-32 years. Mathoera et al, 2000 Calculi Retrospective cohort 89 Bladder neck surgery increases risk of calculi formation Metcalfe et al, 2006 Complications Retrospective cohort 500 Bladder augmentation is a major surgical procedure with significant potential morbidity Nomura et al, 2002 Complications Retrospective cohort 21 Bladder augmentation is an effective treatment method for patients with a neurogenic bladder Mingin et al, 2002 Complications Prospective case control 33 Bladder augmentation is safe and does not negatively affect linear growth Mitsui et al, 2008 Outcome and QoL Mixed methods 22 Benefits of ileocystoplasty were demonstrated with video urodynamics. QoL improved compared to conservative treatments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported outcomes of enterocystoplasty have generally been favorable with respect to increasing bladder capacity, decreasing storage pressures, and improving upper urinary tract drainage 40, 41. Up to 90% achieve socially acceptable urinary continence with or without an additional bladder outlet procedure 40, 42, 43. Notwithstanding, enterocystoplasty has potential serious implications, especially for children with an anticipated longer residual life span than adults because enteric tissue, although incorporated into the bladder, retains its absorptive and secretory properties.…”
Section: Bladder Augmentationmentioning
confidence: 99%
“…Chez le patient blessé médullaire, le reflux traduit surtout un défaut de compliance vésicale ou des lésions anatomiques séquellaires d'un ancien déséquilibre. Même si les patients restent probablement plus à risque de développer des infections urinaires hautes, ils ne sont cependant pas forcément plus à risque de développer une insuffisance rénale si le défaut de compliance de leur réservoir vésical est réglé comme le montrent plusieurs séries d'entérocystoplastie [35,36] (NP 2-4).…”
Section: Outils Diagnostiques : Fonction Rénale Chez Les Patients Bmunclassified